Economic effects of shifting airport activity in the Los Angeles metro region. (September 2021) - Oster, Clinton; Strong, John
Abstract: We estimate the economic effects of a reallocation of passenger traffic from congested Los Angeles International Airport (LAX) to Ontario International Airport (ONT). We find that the relative market shares of the two airports are a function of time and distance, relative fares, and absolute frequencies. Given increasing congestion and population growth patterns, there appears to be potential for expanded operations at Ontario, with resulting economic and environmental benefits. We define the potential market as those travelers choosing LAX despite being closer in travel time and distance to ONT, based on specific postal codes. Using estimates of the value of time, vehicle and aircraft operating costs, and emissions, we calculate the potential effects of shifting both for the average individual passenger and for 10 percent of the potential market from LAX to ONT. These estimated shifts would require only a relatively small percentage change in flight operations. We estimate the value of time and cost savings for both private and ride-sharing services at between 6 million and 11 million annually for a 10 percent shift, depending on whether parking fee differentials are included. The parking fee differentials represent just over half the estimated savings for private vehicle travelers, and to some degree may reflect locational rents rather than resource costs to the overall economy. We also estimate potential reductions in CO2 emissions of more than 4200 tons annually for a 10 percent shift, as well as meaningful reductions in hydrocarbons, CO, and NOx.